Installation and Activation of Fiber To The Home (FTTH) Networks and Macrobending Problems in the Feeder Cable Segment - Yustini; Asril, Aprinal Adila; Setiawan, Herry; Maria, Popy; Rifka, Silfia (Brilliance: Research of Artificial Intelligence, 2023)
Macrobending is a form of disturbance in Fiber To The Home (FTTH) networks that occurs due to macro-level bending of the cable caused by damage to the fiber optic. Macrobending frequently occurs in FTTH networks within the feeder cables. Feeder cables serve as connectors between the Optical Line Terminal (OLT) and Optical Distribution Cabinet (ODC) in the FTTH system. The occurrence of macrobending in feeder cables affects the quality of the FTTH network. In this study, the impact of macrobending is analyzed based on curvature diameters of 50 cm, 25 cm, and 5 cm on feeder cables before and after FTTH network activation. Before FTTH network activation, the High Super Luminescent Diode (HSL) is used as the input power source, whereas after activation, the input power source comes from the OLT using Small Form-factor Pluggable (SFP) modules. The attenuation (loss) before activation due to macrobending, with curvature diameters of 50 cm, 25 cm, and 5 cm, is found to be 0.02 dB, 0.05 dB, and 0.26 dB, respectively. After activation, the attenuation with the same curvature diameters is measured as 0.01 dB, 0.02 dB, and 0.20 dB, respectively. It is observed that as the curvature diameter decreases, the attenuation increases. The comparison of attenuation before and after network activation doesn't show a significant difference because the input power doesn't affect macrobending, rather it is influenced by the curvature diameter.